Prevalence of rifampicin-resistant Mycobacterium tuberculosis among human-immunodeficiency-virus-seropositive patients and their treatment outcomes - C.K. Vidyaraj; A. Chitra; S. Smita; M. Muthuraj; S. Govindarajan; B. Usharani; S. Anbazhagi (Springer, 2019)
Multidrug resistant (MDR) and extensively drug resistant tuberculosis (TB) are a threat to the TB control programs in developing countries, and the situation is worsened by the human immunodeficiency virus (HIV) pandemic. This study was performed to correlate treatment outcome with the resistance patterns in HIV-seropositive patients coinfected with pulmonary TB. Sputum specimens were collected from 1643 HIV-seropositive patients and subjected to microscopy and liquid culture for TB. The smear- and culture-positive Mycobacterium tuberculosis isolates were subjected to Genotype MTBDRplus assay version 2.0. The M. tuberculosis culture-positivity rate was 39.44% (648/1643) among the 1643 HIV-seropositive patients and the overall MDR-TB rate was 5.6% (36/648). There were 421 newly diagnosed and 227 previously treated patients, among whom, MDR-TB was associated with 2.9% and 10.57% cases, respectively. The rate of rifampicin monoresistant TB among the cases of MDR-TB was 2.31% (15/648) and the rate of combined rifampicin and isoniazid resistance was 3.24% (21/648). The cure and death rates among the 20 registered cases were 30% (6/20) and 35% (7/20), respectively. Five cases were on treatment and two cases were defaulters among the 20 registered cases. High death rate (13, 36.1%, 95% confidence interval 20.8-53.8) was observed in this study among the patients who had mutations at the 530-533 codons. The present study emphasized the prerequisite to monitor the trend of drug-resistant TB in various mutant populations in order to timely implement appropriate interventions to curb the threat of MDR-TB.